Corpus linguistics for translation and contrastive studies a guide for research - Mikhailov, Mikhail (Translator); Cooper, Robert (English lecturer) (Routledge corpus linguistics guides, 2016)
Corpus Linguistics for Translation and Contrastive Studies provides a clear and practical introduction to using corpora in these fields. Giving special attention to parallel corpora, which are collections of texts in two or more languages, and demonstrating the potential benefits for multilingual corpus linguistics research to both translators and researchers